The Role of Technological Vigilance in Achieng Entrepreneurship For Companies Pharmaceutical Industry in Syrian coast - الخير, عبير; بسام زاهر; ريزان نصور (Latakia University Journal - Economic and Legal Sciences Series, 2025)
Pharmaceutical companies today operate in an era dominated by many threats and challenges. They have become operating within a competitive environment that requires a high degree of vigilance in the steps they take to achieve their goals. In order to continue to achieve leadership in their business and increase their ability to create and innovate, they must rely on a Technological vigilance system that works. To receive information that helps them discover what might happen, when, and where it will happen. The mission of technological vigilance is not only to collect information and knowledge, but also to research scientific innovations and technological innovations in various fields. Practicing any industry requires an advanced level of technology that improves its pioneering performance and makes it capable of inventing new products. The research aimed to study the role of Technological Vigilance in Entrepreneurship dimensions (Innovativeness, Autonomy, Risk Taking) Companies Pharmaceutical Industry in Syrian coast. The researcher adopted the statistical method, and the preliminary data were collected through a questionnaire form as a tool for study, which was organized based on the researcher's knowledge of published literature, questionnaire was distributed to a sample of research that represented by 85. In order to test hypotheses, the researcher unloaded a database using SPSS issue 23 and adopted on Cronbach's Alpha to measure the stability of the meter. The most important results of the research were the existence of a moral relationship between technological Vigilance and achieving the dimensions of entrepreneurship, in the companies under study, which are (Innovation - Autonomy - Risk) in the companies under research. .